Updating the Antimicrobial Resistance Pattern among Critical Priority Pathogens in the Intensive Care Unit in Northern Iran Post COVID-19 Pandemic - Golnar Rahimzadeh; Nadia Ghezljai; Shaghayegh Rezai; Raha Rezai; Mohammad Reza Navaiefar; Mohammad Sadegh Rezai; Masoud Moradi; Mostafa Shakeri (Advanced Biomedical Research)
Background: During the COVID-19 pandemic, the widespread and indiscriminate prescription of antibiotics led to a significant increase in antibiotic resistance and the emergence of multi-drug-resistant (MDR) strains. This study aims to evaluate the prevalence of antibiotic resistance in MDR Gram-negative isolates in the intensive care unit (ICU) of northern hospitals in Iran following the COVID-19 pandemic. Materials and Methods: This is a cross-sectional study. The samples were collected from patients with healthcare-associated infections at ICU of hospitals in northern Iran. Antimicrobial resistance was assessed using standard broth macrodilution, and resistance genes were accurately identified using the multiplex polymerase chain reaction method. Results: The present study revealed that the ICU had the highest frequency of MDR Acinetobacter baumannii infections (32.1%) and the lowest frequency of E. coli infections (12.6%). The frequency of resistance genes of A. baumannii is as follows: bla OXA-51 (100%), ampC (99.12%), apA6 (90.35%), and blaNDM (69.30%). Co-amoxiclav showed a 100% resistance rate, while Piperacillin-tazobactam had the lowest resistance rate at 38.2%. Conclusions: This study identified a high prevalence of MDR A. baumannii in ICU patients with healthcare-associated infections at northern hospitals in Iran, following COVID-19. Recommended treatments include Piperacillin-tazobactam or Meropenem.